Investigation of Remazol Brilliant Blue R removal in batch and fixed bed column reactor systems by MnOx: Non-linear isotherm and kinetic modelling - Yardimci, Aynur; Tepe, Ozlem (Elsevier, 2024)
Remazol Brilliant Blue R (RBBR) is a dye frequently used in the textile industry. Discharging industrial effluents containing dye residues could pose a risk to biological systems. In the present study, the removal of RBBR from aqueous solutions was tested using MnOx in both batch and continuous systems. The effects of various parameters, including the solution's initial pH, the amount of MnOx, the initial RBBR concentration, and temperature on RBBR removal by MnOx, were investigated. The optimum pH and MnOx amount at an initial RBBR concentration of 50 mg/L and 30 degrees C were pH 7 and 0.3 g/L, respectively, resulting in an RBBR removal efficiency of 94.43 %. The adsorption capacity was found to be 227.06 mg/g at an initial RBBR concentration of 100 mg/L, pH 7, and 30 degrees C. The adsorption process best fit the non-linear Langmuir isotherm and Elovich kinetic models, with the least error distributions and it was characterized as exothermic and spontaneous. The activation energy value was calculated to be 92.06 kJ/mol. In the fixed bed column reactor, the equilibrium uptake (qe) was 196.30 mg at an RBBR concentration of 200 mg/L and a flow rate of 3.70 mL/min. The results imply that MnOx shows great promise for wastewater treatment contaminated with dyes.
Keywords: MnOx; Non-linear kinetic and isotherm models; RBBR dye; Removal